Research on three-stage hybrid optimization control of the three-level half-bridge LLC resonant converter - Wang, Junrui; Chen, Jianfei; Zhao, Dongqi; Qin, Hao; Li, Ruiqi (Scientific reports, 2025)
With the rise of the charging level of new energy vehicles, the three-level half-bridge LLC topology is gradually applied to the rear stage of DC charging pile. This topology often adopts a hybrid control mode of Pulse Frequency Modulation (PFM) and Phase Shift Modulation (PSM) to obtain a wide output range. However, the PFM and PSM hybrid control can not meet the Zero Voltage Switch (ZVS) of the inner tube at the low voltage output. In order to solve this problem, this paper analyses the conditions of LLC to achieve ZVS, and proposes a Variable Frequency Burst Modulation (VFBM) to maintain dead time and minimum effective duty cycle, and forms a three-stage hybrid optimization control strategy with PSM and PFM, and sets three mode switching points to make the system work in different control modes under different output levels. Finally, the simulation model of fixed input 600 V and output 150 ~ 650 V was established by Matlab/Simulink to verify that the three-stage hybrid optimization control strategy can not only realize the inner tube ZVS in low voltage interval, but also realize the wide output voltage range, which improves the efficiency of the system. And can accurately switch the working mode, so that the post-stage system output stable, continuous and adjustable DC voltage.